A TiO2 nanorod-modified SiNWs hierarchical array anode, its preparation method and application
Patent Information
- Application Number
- CN202611357349.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-03
- Publication Date
- 2026-10-30
AI Technical Summary
(1)通过金属辅助化学刻蚀在硅基底表面原位形成Si NWs阵列,构建开放的三维反应界面,提高电解液浸润性和界面反应均匀性,并为硅氧化产物的迁移与溶解提供空间。
Smart Images

Figure CN123017847A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the fields of silicon-air batteries and semiconductor electrode interface protection technology, specifically to a TiO2 nanorod modified Si NWs hierarchical array structure anode, its preparation method, and a silicon-air battery containing the anode. Background Technology
[0002] Silicon-air batteries use silicon as the negative electrode active material and oxygen from the air as the positive electrode active material. They are characterized by abundant silicon resources, high theoretical specific capacity and theoretical energy density, good safety, and environmental friendliness. Alkaline electrolytes, with their low cost and high ionic conductivity, are commonly used electrolyte systems in silicon-air batteries.
[0003] However, silicon undergoes targeted electrochemical oxidation, chemical self-corrosion, and hydrogen evolution reaction simultaneously in alkaline media. Silicon oxides, silanol compounds, or silicates generated during discharge may also accumulate locally on the anode surface, forming a high-resistivity passivation layer. This leads to impeded interfacial charge transfer, decreased discharge voltage, and reduced silicon utilization.
[0004] Constructing Si NWs arrays through metal-assisted chemical etching can increase the effective reaction area of the silicon anode and provide space for the dissolution and migration of reaction products. However, the high specific surface area will also increase the contact area between silicon and water and hydroxide ions, which may exacerbate non-target corrosion, hydrogen evolution and local structural damage.
[0005] TiO2 exhibits good chemical stability and interfacial passivation capabilities, making it suitable for isolating silicon from direct contact with electrolytes. However, a continuous and dense TiO2 film may restrict electrolyte wetting, ion migration, and the removal of silicon oxidation products. Therefore, a Si / TiO2 composite structure that combines interfacial protection with open mass transfer channels is needed.
[0006] Existing technologies have reported the growth of TiO2 nanorods on planar silicon wafers or conductive glass, as well as the formation of TiO2 coating layers on the surface of silicon particles. However, for the corrosion-passivation synergy problem of Si NWs in alkaline silicon-air batteries, there is still a lack of hierarchical TiO2 nanorod modification structures that take into account adhesion stability, structural openness, and interface protection capabilities. Summary of the Invention
[0007] Silicon-air batteries possess advantages such as high theoretical energy density, abundant silicon resources, and environmental friendliness. However, silicon anodes are prone to self-corrosion, hydrogen evolution, and uneven passivation in alkaline electrolytes, leading to interfacial instability and reduced discharge performance. Therefore, this invention aims to construct a structurally stable, open-channel TiO2 nanorod-modified Si NWs hierarchical array anode to reduce direct contact between silicon and the electrolyte, improve interfacial stability, and enhance the discharge performance of silicon-air batteries.
[0008] To achieve the above objectives, the present invention provides the following technical solution: In a first aspect, the present invention provides a TiO2 nanorod modified Si NWs hierarchical array structure anode, comprising: a silicon substrate, a Si NWs array integrally connected to the silicon substrate, a TiO2 seed layer formed on the surface of the Si NWs, and TiO2 nanorods grown on the TiO2 seed layer.
[0009] In this invention, TiO2 seed layers are pre-formed on the surface of Si NWs, and TiO2 nanorods are hydrothermally grown using TiO2 seed layers as nucleation sites. This allows TiO2 to form a stable hierarchical composite interface with Si NWs, thereby reducing the degree of local direct contact between silicon and alkaline electrolyte, alleviating self-corrosion, hydrogen evolution, and uneven passivation, while retaining open channels for electrolyte entry and migration of soluble reaction products.
[0010] Preferably, the silicon substrate is a boron-doped p-type silicon wafer or a phosphorus-doped n-type silicon wafer; the TiO2 nanorods are rutile phase.
[0011] Preferably, the average length of the Si NWs is 9.8 μm; the average length of the TiO2 nanorods is 487 nm, and the TiO2 nanorods grow cross-connectedly in the surface of the Si NWs array and in the gaps between the nanowires to form a hierarchical network structure with open pores.
[0012] The Si NWs array is grown in situ on the silicon substrate surface via metal-assisted chemical etching, integrally connected with the silicon substrate to construct an open three-dimensional reaction interface. This increases the effective reaction area of the silicon anode, provides space for the dissolution and migration of silicon oxide products, and improves electrolyte wettability and interfacial reaction uniformity. A Si NWs length of 9.8 μm provides sufficient specific surface area while maintaining the integrity of the array structure. Excessively long Si NWs can exacerbate mechanical instability and corrosion exposure, while excessively short ones result in insufficient reaction area gain. The TiO2 seed layer is formed on the Si NWs surface, providing dense and uniform nucleation sites to guide the in-situ and uniform nucleation and growth of TiO2 on the silicon surface during subsequent hydrothermal reactions. This avoids the problem of TiO2's difficulty in adhering and growing on the Si NWs surface without a seed layer, improves the interfacial bonding stability between TiO2 nanorods and Si NWs, and reduces the risk of localized TiO2 agglomeration or detachment from the silicon surface. The TiO2 nanorods grow on a seed layer using TiO2 seeds as nucleation sites, forming a cross-connected, open-pore hierarchical network structure with Si NWs. On one hand, the rutile phase TiO2 exhibits good chemical stability, partially isolating silicon from direct contact with the alkaline electrolyte and mitigating self-corrosion and hydrogen evolution reactions of the silicon anode. On the other hand, the open pores retain channels for electrolyte entry and soluble reaction products to migrate outward, avoiding the problem of mass transfer being restricted by continuous, dense films. Simultaneously, the cross-connected structure provides mechanical support to the Si NWs array, mitigating nanowire thinning, breakage, collapse, and localized detachment during discharge. With an average length of 487 nm, the TiO2 nanorods can form an effective interface protective layer while retaining sufficient open pores, preventing excessive nanorod growth that could block mass transfer channels.
[0013] Secondly, the present invention provides a method for preparing the above-mentioned TiO2 nanorod modified Si NWs hierarchical array structure anode, comprising the following steps: (1) Silicon wafer pretreatment: Cleaning and removing the surface oxide layer from the silicon wafer; (2) Silver-assisted chemical etching: The treated silicon wafer is placed in a mixture of silver nitrate and hydrofluoric acid for metal-assisted chemical etching to form a Si NWs array integrally connected with the silicon substrate; (3) Preparation of TiO2 seed layer: The titanium-containing precursor liquid is spin-coated onto the surface of the Si NWs array and heat-treated at 450~550℃ to form TiO2 seed layer; (4) Hydrothermal growth of TiO2 nanorods: Si NWs samples with TiO2 seed layers are placed in a hydrothermal reaction solution containing titanium source and hydrochloric acid, and hydrothermal reaction is carried out at 150~170℃. After cleaning and drying, the TiO2 nanorod modified Si NWs hierarchical array structure anode is obtained.
[0014] The preparation process flow chart is shown below. Figure 1 .
[0015] Preferably, in step (1), the silicon wafer pretreatment includes: ultrasonically cleaning the silicon wafer in methanol and ethanol for 2-10 min in sequence; treating it in a mixture of concentrated sulfuric acid and hydrogen peroxide in a volume ratio of 3:1 for 100-150 min; and then treating it in a mixture of 40wt.% hydrofluoric acid and water in a volume ratio of 1:3 for 5-10 min to remove the natural oxide layer on the surface.
[0016] Preferably, in step (2), the concentration of silver nitrate is 0.01~0.03 M; the concentration of hydrofluoric acid is 2~3 M; the metal-assisted chemical etching is performed at room temperature for 100~150 min; after etching, the silicon wafer is placed in nitric acid for 4~6 min to remove residual silver.
[0017] Preferably, in step (3), the titanium-containing precursor solution is composed of tetrabutyl titanate, acetylacetone, water, polyvinylpyrrolidone, and ethanol, wherein the molar ratio of acetylacetone, tetrabutyl titanate, and water is 0.2~0.5:1:0.5~2; the concentration of tetrabutyl titanate is 0.02~0.05 M; the concentration of polyvinylpyrrolidone is 10~100 mg / L; the spin coating speed is 3000~10000 rpm; the spin coating time is 20~60 s; the heat treatment temperature is 450~550℃; and the heat treatment time is 1~3 h.
[0018] Preferably, in step (4), the hydrothermal reaction solution is composed of hydrochloric acid, deionized water, and tetrabutyl titanate, with a nominal concentration of 0.036~0.055 mol / L; the volume ratio of deionized water to concentrated hydrochloric acid is 0.8~1.2:1; the hydrothermal reaction time is 1.5~3 h, and the hydrothermal temperature is 150-170℃; the Si NWs sample with the TiO2 seed layer is placed vertically in the reaction vessel to reduce the sedimentation of homogeneous particles in the solution on the electrode surface. However, this is not limited to the values listed above; other unlisted values within the above ranges are also applicable.
[0019] Preferably, after the reaction in step (4) is completed, the reaction vessel is rapidly cooled by rinsing with cold water or by natural cooling, and the sample is taken out and rinsed with ethanol and deionized water in sequence and then dried.
[0020] In the above preparation method: the silicon wafer pretreatment in step (1) can remove organic contaminants and natural oxide layer on the silicon wafer surface, providing a clean and fresh silicon surface for subsequent metal-assisted chemical etching, and ensuring the uniformity of etching. In step (2), metal-assisted chemical etching is performed with a mixture of silver nitrate and hydrofluoric acid. Silver nanoparticles are deposited on the silicon surface and act as a catalyst. The silicon crystal direction is selectively etched to form a Si NWs array integrally connected with the silicon substrate. The etching is performed at room temperature. When the etching time is 100-150 min, a Si NWs array with a length of about 9.8 μm can be obtained. After the etching is completed, the residual silver is removed with nitric acid to avoid the residual metallic silver affecting the anode interface performance. In step (3), a titanium-containing precursor liquid is spin-coated onto the surface of the Si NWs array and heat-treated at 450~550℃ to form a TiO2 seed layer. This seed layer provides dense and uniform nucleation sites for subsequent hydrothermal growth and improves the bonding stability between TiO2 nanorods and Si NWs. The thickness and uniformity of the seed layer can be controlled by adjusting the spin-coating speed, spin-coating times, and heat treatment temperature and time. In step (4), the Si NWs sample with TiO2 seed layer is placed vertically in a hydrothermal reaction solution containing titanium source and hydrochloric acid, and hydrothermal reaction is carried out at 150-170℃. Rutile TiO2 nanorods are grown in situ on the surface of Si NWs using TiO2 seed as nucleation sites. Vertical placement can reduce the sedimentation of homogeneous particles in the solution on the electrode surface and improve the uniformity of in-situ growth of TiO2 nanorods. The combination of hydrothermal temperature and time is controlled within the stable growth range of rutile TiO2. If the temperature is too low or the time is too short, the crystallization will be insufficient. If the temperature is too high or the time is too long, the nanorods will grow excessively and block the pores. After the reaction, rapid cooling by rinsing with cold water can inhibit the further growth of homogeneous particles in the hydrothermal solution and retain the uniform and slender morphology of the nanorods. Natural cooling helps to obtain a nanorod structure with higher coverage.
[0021] Thirdly, the present invention provides a silicon-air battery, comprising the above-mentioned TiO2 nanorod modified Si NWs hierarchical array structure anode, an air cathode, a separator disposed between the anode and the air cathode, and an alkaline electrolyte.
[0022] Preferably, the alkaline electrolyte is 3 M KOH; the TiO2 nanorod side of the TiO2 nanorod modified Si NWs hierarchical array anode faces the electrolyte.
[0023] Fourthly, the present invention provides the application of the above-mentioned TiO2 nanorod modified Si NWs hierarchical array structure anode in suppressing self-corrosion, hydrogen evolution and uneven passivation of silicon anodes in alkaline silicon-air batteries.
[0024] Compared with the prior art, the present invention has the following beneficial effects: (1) A Si NWs array is formed in situ on the surface of a silicon substrate by metal-assisted chemical etching, which builds an open three-dimensional reaction interface, improves the wettability of the electrolyte and the uniformity of the interface reaction, and provides space for the migration and dissolution of silicon oxide products.
[0025] (2) The TiO2 seed layer improves the nucleation uniformity and interfacial adhesion of nanorods, reducing the risk that TiO2 will only agglomerate locally or fall off the silicon surface during hydrothermal growth.
[0026] (3) TiO2 nanorods and Si NWs form a hierarchical open network, which can partially isolate the direct contact between silicon and alkaline electrolyte, and alleviate self-corrosion and hydrogen evolution; at the same time, the open pores are conducive to electrolyte wetting and the outward migration of silicate reaction products.
[0027] (4) The cross-connected structure formed by TiO2 nanorods can improve the mechanical support and interface stability of Si NWs arrays, and slow down the thinning, breakage, collapse and local shedding of nanowires during the discharge process.
[0028] (5) The preparation methods are mainly spin coating, heat treatment and hydrothermal reaction. The equipment requirements are low, the process parameters are adjustable, and it is suitable for silicon substrates with different doping types and sizes. Attached Figure Description
[0029] Figure 1 This is a flowchart illustrating the preparation process of the TiO2 nanorod-modified Si NWs anode of the present invention. Figure 2 The XRD pattern of p-type Si NWs@ TiO2 prepared in Example 1; Figure 3 SEM image (A) and EDS energy spectrum (B) of p-type Si NWs@ TiO2 prepared in Example 1; Figure 4 The cross-section (A) of p-type Si NWs and the planar image (B) of p-type Si NWs@ TiO2 obtained in Example 1 are shown. Figure 5 SEM image (A) and EDS energy spectrum (B) of p-type Si NWs@ TiO2 prepared in Example 2; Figure 6 SEM image (A) and EDS energy spectrum (B) of p-type Si NWs@ TiO2 prepared in Example 3; Figure 7 SEM image (A) and EDS energy spectrum (B) of p-type Si NWs@ TiO2 were obtained for Comparative Example 1. Figure 8SEM images of p-type Si NWs prepared for Comparative Example 2; Figure 9 SEM image (A) and EDS energy spectrum (B) of p-type Si NWs@TiO2 in Comparative Example 3. Figure 10 This is a comparison diagram of the Tafel polarization curves of Example 1 and Comparative Example 2 in this invention; Figure 11 This is a comparison chart of the power density of the anode in an aqueous silicon-air battery in Example 1 and Comparative Example 2 of this invention. Detailed Implementation
[0030] To enable those skilled in the art to better understand the technical solutions of the present invention, the present invention will be described in detail below with reference to specific embodiments. Experimental methods in the following embodiments that do not specify specific conditions are generally performed under conventional conditions or as recommended by the manufacturer. Unless otherwise defined, all technical and scientific terms used herein have the same meaning as known to those skilled in the art. Furthermore, any methods and materials similar to or equivalent to those described herein can be applied to the present invention. The preferred embodiments and materials described herein are for illustrative purposes only. The present invention relates to highly corrosive reagents such as concentrated sulfuric acid, hydrogen peroxide, hydrofluoric acid, nitric acid, and concentrated hydrochloric acid; related operations should be carried out under conditions with corrosion-resistant ventilation facilities and appropriate safety protection.
[0031] The endpoints and any values of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of the various ranges, the endpoint values of the various ranges and individual point values, and individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.
[0032] To facilitate understanding of this invention, some terms and abbreviations used in this application are explained. It should be noted that these explanations are for comprehension purposes only and should not be construed as limiting the invention.
[0033] TiO2: Titanium dioxide, a wide-bandgap semiconductor material, has the characteristics of good chemical stability, non-toxicity, and low cost; rutile phase is its thermodynamically stable crystal phase, with excellent chemical stability and interface passivation ability. In this application, TiO2 nanorods are preferably rutile phase.
[0034] Si NWs: Silicon Nanowires, in this application, refers to a one-dimensional silicon nanostructure array formed in situ on the surface of a silicon substrate by metal-assisted chemical etching and integrally connected with the silicon substrate.
[0035] Metal-Assisted Chemical Etching (MACE): A method that uses noble metal (such as silver) nanoparticles as catalysts to selectively etch silicon in a solution containing HF through metal-semiconductor microcouples, which can construct vertically arranged nanowire arrays on the silicon surface.
[0036] TiO2 seed layer: A nano-TiO2 grain layer formed on the surface of Si NWs by spin coating and heat treatment with titanium-containing precursor liquid, which provides nucleation sites for subsequent hydrothermal growth.
[0037] Hydrothermal reaction: A chemical synthesis reaction carried out in a closed reactor with water as a solvent at a temperature above 100°C. It is often used for the controlled growth of nanomaterials.
[0038] Rutile phase: a crystal form of TiO2 (tetragonal system), which is listed alongside anatase and brookite phases and is a thermodynamically stable phase of TiO2.
[0039] Alkaline electrolyte: An aqueous solution with an alkali (such as KOH) as a solute. In this application, the alkaline electrolyte used in silicon-air batteries is preferably a 3 M KOH solution.
[0040] Silicon-air battery: A battery system that uses silicon as the negative electrode active material and oxygen from the air as the positive electrode active material.
[0041] Passivation layer: When a silicon anode discharges in an alkaline electrolyte, the discharge products (silicon oxides, silanol compounds, silicates) accumulate locally on the surface, forming a high-resistivity layer that hinders the transfer of interfacial charges.
[0042] Self-corrosion: The spontaneous oxidation and dissolution reaction of silicon in an alkaline electrolyte without an applied current.
[0043] Hydrogen evolution reaction: A side reaction in which silicon reacts with water or hydroxide ions to produce hydrogen gas, which occurs alongside self-corrosion.
[0044] Tafel polarization curve: A curve describing the logarithmic relationship between electrode overpotential and current density, which can be used to evaluate the corrosion potential and corrosion rate of the electrode; the more positive the corrosion potential, the more corrosion resistant the electrode.
[0045] Three-electrode system: An electrochemical testing system consisting of a working electrode, a counter electrode, and a reference electrode. In this application, the Hg / HgO electrode is used as the reference electrode.
[0046] Pt / C catalyst: A platinum catalyst supported on a carbon support, used in this application as an oxygen reduction catalyst for the air cathode.
[0047] Gas diffusion electrode: An electrode structure that allows gas (such as air) to diffuse to catalytically active sites, which is used as the air cathode of a silicon-air battery in this application.
[0048] Diaphragm: A porous membrane placed between the anode and cathode to isolate the two electrodes and allow ion conduction.
[0049] Cross-connected structure: TiO2 nanorods intersect and overlap with each other on the surface of Si NWs and in the gaps between nanowires to form a network structure.
[0050] Open pores: The pore channels preserved in the TiO2 nanorod hierarchical network and connected to the outside world provide pathways for electrolyte wetting and reaction product migration.
[0051] Example 1 This embodiment provides a TiO2 nanorod-modified Si NWs hierarchical array anode, comprising: a silicon substrate, a Si NWs array integrally connected to the silicon substrate, a TiO2 seed layer formed on the surface of the Si NWs, and TiO2 nanorods grown on the TiO2 seed layer; wherein the Si NWs have a length of approximately 9.8 μm, and the TiO2 nanorods are rutile phase with an average length of approximately 487 nm, growing cross-connectedly on the surface of the Si NWs array and in the gaps between the nanowires to form a hierarchical network structure with open pores.
[0052] The above-mentioned method for preparing the anode includes the following steps: (1) Silicon wafer pretreatment: p-type silicon wafers were selected and cut according to the required electrode size. The silicon wafers were ultrasonically immersed in methanol for 10 min and then ultrasonically immersed in ethanol for 10 min to remove surface organic contaminants. The silicon wafers were treated in a mixture of concentrated sulfuric acid and hydrogen peroxide at a volume ratio of 3:1 for 120 min, and then rinsed thoroughly with deionized water. The silicon wafers were then immersed in a mixture of 40 wt.% hydrofluoric acid (HF) and water at a volume ratio of 1:3 for 10 min to remove the natural oxide layer on the surface. The treated silicon wafers were then ultrasonically cleaned sequentially with deionized water, methanol, and ethanol.
[0053] (2) Preparation of Si NWs array by metal-assisted chemical etching: Prepare 0.02 M AgNO3 solution and 6 M HF solution respectively, and mix them at a volume ratio of 1:1 to obtain a mixed solution. Place the silicon wafer with the polished side facing up in the mixed solution and etch at room temperature for 150 min. After etching, rinse with deionized water, place the silicon wafer in nitric acid for 5 min to remove residual silver, rinse again with deionized water and dry to obtain a Si NWs array integrally connected to the silicon substrate.
[0054] (3) Preparation of TiO2 seed layer: Prepare 10 mL of TiO2 seed titanium-containing precursor solution: the molar ratio of acetylacetone, tetrabutyl titanate and water is about 0.3:1:1, the concentration of tetrabutyl titanate is 0.05 M, and the concentration of polyvinylpyrrolidone is 40 mg / L. Stir the above precursor solution until clear. Drop the precursor solution onto the etched Si NWs array surface, spin coat at 8000 rpm for 60 s, spin coat 5 times; then place the sample in a muffle furnace and heat treat at 500℃ for 2 h in air atmosphere to obtain Si NWs array with TiO2 nanocrystal seed layer.
[0055] (4) Hydrothermal growth of TiO2 nanorods: 20 mL of deionized water and 20 mL of HCl were added to a beaker and stirred for 5 min under ice bath conditions. 665 μL of tetrabutyl titanate was added, and the solution was stirred until clear or a homogeneous and transparent system was formed. The solution was transferred to a polytetrafluoroethylene-lined reactor. The Si NWs sample containing the TiO2 seed layer was placed vertically in the liner, the reactor was sealed, and hydrothermal reaction was carried out at 160 °C for 2 h. After the reaction, the reactor was rinsed with cold water to cool it rapidly. The sample was taken out and rinsed thoroughly with ethanol and deionized water in sequence, and dried in air to obtain the TiO2 nanorod-modified Si NWs anode, denoted as p-type Si NWs@TiO2.
[0056] Scanning electron microscopy (SEM) revealed that TiO2 nanorods grew on the surface of the Si NWs array and within the gaps between the nanowires, forming a relatively dense yet still open and interconnected structure (see [link to SEM]). Figure 3 (See A). EDS energy dispersive spectroscopy analysis showed the presence of Ti, O, and Si elements on the sample surface, indicating that TiO2 was successfully grown on the Si NWs surface (see A). Figure 3 B), measurements and statistics based on cross-sectional and surface SEM images show that the length of Si NWs is approximately 9.8 μm, and the average length of TiO2 nanorods is approximately 487 nm (see B). Figure 4 (A and B). Crystal phase analysis showed that the TiO2 nanorods exhibited a rutile phase (see [reference]). Figure 2 ).
[0057] Example 2 This embodiment provides a TiO2 nanorod-modified Si NWs hierarchical array anode, with the same structural composition as in Embodiment 1, including: a silicon substrate, a Si NWs array integrally connected to the silicon substrate, a TiO2 seed layer formed on the surface of the Si NWs, and TiO2 nanorods grown on the TiO2 seed layer; the TiO2 nanorods grow cross-connectedly on the surface of the Si NWs array and in the gaps between the nanowires, forming a hierarchical network structure with open pores.
[0058] The anode was prepared as follows, differing from Example 1 in that: in step (1), the ultrasonic time for methanol and ethanol was 5 min each, and the mixture of 40 wt.% HF and water in a volume ratio of 1:3 was treated for 5 min; in step (2), the HF concentration was 5 M, and the etching time was 120 min; in step (3), the spin coating was performed 6 times, and the heat treatment was carried out at 500℃ for 90 min; in step (4), 500 μL of tetrabutyl titanate was added, and the anode was rapidly cooled by rinsing with cold water after the hydrothermal reaction was completed. The remaining steps were the same as in Example 1.
[0059] TiO2 nanorods were used to modify Si NWs anodes, which were denoted as p-type Si NWs@TiO2.
[0060] Scanning electron microscopy (SEM) revealed that TiO2 nanorods grew on the surface of the Si NWs array and within the gaps between the nanowires, with a higher degree of coverage by the TiO2 nanorods (see [link to SEM]). Figure 5 A), EDS energy dispersive spectroscopy analysis showed the detection of characteristic elements Ti, O, and Si, confirming the presence of a high-coverage TiO2 modification layer (see A). Figure 5 B).
[0062] Example 3 This embodiment provides a TiO2 nanorod-modified Si NWs hierarchical array anode, with the same structural composition as in Embodiment 1, including: a silicon substrate, a Si NWs array integrally connected to the silicon substrate, a TiO2 seed layer formed on the surface of the Si NWs, and TiO2 nanorods grown on the TiO2 seed layer; the TiO2 nanorods grow cross-connectedly on the surface of the Si NWs array and in the gaps between the nanowires, forming a hierarchical network structure with open pores.
[0063] The anode was prepared as follows, differing from Example 1 in that: in step (1), the ultrasonic treatment time for methanol and ethanol was 2 min each, the treatment with a mixture of concentrated sulfuric acid and hydrogen peroxide was 100 min, and the treatment with a mixture of 40 wt.% HF and water in a volume ratio of 1:3 was 5 min; in step (2), the HF concentration was 4 M, and the etching time was 150 min; in step (3), the spin coating time was 40 s, the spin coating was performed 3 times, and the heat treatment was carried out at 500℃ for 2 h; in step (4), 665 μL of tetrabutyl titanate was added, and the mixture was allowed to cool naturally after the hydrothermal reaction was completed. The remaining steps were the same as in Example 1.
[0064] TiO2 nanorods were used to modify Si NWs anodes, which were denoted as p-type Si NWs@TiO2.
[0065] Scanning electron microscopy (SEM) revealed that TiO2 nanorods grew on the surface of the Si NWs array and within the gaps between the nanowires, but the coverage of silicon was insufficient, resulting in a significant amount of exposed silicon (see [link to SEM]). Figure 6 A), EDS energy dispersive spectroscopy analysis showed a high proportion of Si elemental signal, corresponding to a large amount of exposed silicon substrate on the sample surface (see...). Figure 6 B).
[0066] Comparative Example 1 Direct hydrothermal treatment of Si NWs without TiO2 seed layer: Step (1) silicon wafer pretreatment and step (2) metal-assisted chemical etching are the same as in Example 1 to obtain Si NWs array. Step (3) is omitted. Without seed layer preparation, the Si NWs sample without TiO2 seed layer treatment is placed vertically in a reaction vessel containing 20 mL deionized water, 20 mL HCl and 665 μL tetrabutyl titanate hydrothermal reaction solution, and hydrothermally reacted at 160℃ for 2 h. After the reaction, the sample is rinsed with cold water and cooled quickly. The sample is taken out and thoroughly rinsed with ethanol and deionized water in sequence, and dried in air. It is recorded as p-type Si NWs@TiO2.
[0067] Scanning electron microscopy (SEM) revealed that, due to the absence of nano-TiO2 seed preparation, no TiO2 characteristics were detected on the p-type Si NWs after the hydrothermal reaction (see...). Figure 7 A), EDS energy dispersive spectroscopy analysis showed a very weak Ti element signal, proving that almost no TiO2 nucleated and grew on the silicon nanowire surface (see A). Figure 7 B).
[0068] Comparative Example 2 Si NWs without TiO2 nanorods: Step (1) silicon wafer pretreatment and step (2) metal-assisted chemical etching are the same as in Example 1, except that TiO2 seed layer preparation and TiO2 nanorod hydrothermal growth are not performed. A Si NWs array integrally connected to the silicon substrate is obtained, and its SEM is shown in [image missing]. Figure 8 .
[0069] Comparative Example 3 Si NWs@TiO2 that remained in the hot mother liquor for an extended period after the hydrothermal reaction: Step (1) silicon wafer pretreatment, step (2) metal-assisted chemical etching, step (3) TiO2 seed layer preparation, and step (4) TiO2 nanorod hydrothermal growth were all the same as in Example 1. The difference was that after the sample completed the hydrothermal reaction at 160 °C for 2 h, it was not immediately cooled by rinsing with cold water, nor was it immediately removed from the reactor. Instead, the sample was kept in the hot mother liquor for 12 h after the reaction. Then the sample was removed, rinsed thoroughly with ethanol and deionized water in sequence, and dried in air to obtain p-type Si NWs@TiO2 with extended treatment.
[0070] Scanning electron microscopy (SEM) revealed that, compared to normally prepared samples, the excessively long reaction settling time caused localized agglomeration of the nanorods, accompanied by the formation of a small amount of irregular blocky impurities on the surface. The originally open pore structure was partially filled (see...). Figure 9 A), EDS energy dispersive spectroscopy analysis showed the detection of Ti, O, and Si elements, indicating that the sample is still a TiO2-modified SiNWs system (see A). Figure 9 B).
[0071] Test Example 1: Electrochemical Test 1. Test Object The p-type Si NWs / TiO2 composite anode prepared in Example 1 and the p-type SiNWs anode prepared in Comparative Example 2 were used as test objects, respectively.
[0072] 2. Testing Methods Construction of the three-electrode system: The anode under test was used as the working electrode, the graphite electrode as the counter electrode, and the Hg / HgO electrode as the reference electrode. An electrochemical workstation was used to construct the three-electrode system. The electrolyte was a 3 M KOH solution, the test temperature was 25 °C, and the geometric area of contact between each working electrode and the electrolyte was kept consistent.
[0073] The test potential range is 0.8 ~ 1.6 V (relative to Hg / HgO electrode), scan rate 2 mV s 1 .
[0074] 3. Test Results Test results are as follows Figure 10 As shown. Compared to Comparative Example 2, Example 1 exhibits a more positive corrosion potential, indicating that TiO2 nanowires can effectively suppress the self-corrosion and hydrogen evolution reaction of the silicon anode.
[0075] Test Example 2: Power Density Test 1. Test Object Silicon-air batteries were assembled using the p-type Si NWs / TiO2 composite anode prepared in Example 1 and the p-type Si NWs anode prepared in Comparative Example 2, respectively.
[0076] 2. Battery Assembly (1) Anode: Anodes prepared in Example 1 and Comparative Example 2 were used respectively, and the effective area of the anode was kept consistent.
[0077] (2) Air cathode: A gas diffusion electrode with a Pt / C catalyst loaded at a loading of 1.5 mg cm⁻¹ is used. 2 .
[0078] (3) Assembly conditions: battery box with electrode spacing of 15mm ± 1mm, test temperature of 20℃ ± 2℃, and 3 MKOH standard electrolyte as test electrolyte. 3. Test Results Test results are as follows Figure 11 As shown, the silicon-air battery assembled in Example 1 exhibits a higher peak power density than that of Comparative Example 2, indicating that the hierarchical composite interface formed by the etched Si NWs array and the in-situ grown TiO2 nanorods is beneficial for reducing local direct contact and improving peak power output.
[0079] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A TiO2 nanorod-modified Si NWs hierarchical array anode, characterized in that, include: A silicon substrate, a Si NWs array integrally connected to the silicon substrate, a TiO2 seed layer formed on the surface of the Si NWs, and TiO2 nanorods grown on the TiO2 seed layer.
2. The TiO2 nanorod-modified Si NWs hierarchical array structure anode according to claim 1, characterized in that, The silicon substrate is a boron-doped p-type silicon wafer or a phosphorus-doped n-type silicon wafer; the TiO2 nanorods are rutile phase.
3. The TiO2 nanorod-modified Si NWs hierarchical array structure anode according to claim 1, characterized in that, The average length of the Si NWs is 9.8 μm; the average length of the TiO2 nanorods is 487 nm. The TiO2 nanorods grow cross-connectedly on the surface of the Si NWs array and in the gaps between the nanowires, forming a hierarchical network structure with open pores.
4. A method for preparing the TiO2 nanorod modified Si NWs hierarchical array structure anode according to any one of claims 1-3, characterized in that, Includes the following steps: (1) Silicon wafer pretreatment: Cleaning and removing the surface oxide layer from the silicon wafer; (2) Silver-assisted chemical etching: The treated silicon wafer is placed in a mixture of silver nitrate and hydrofluoric acid for metal-assisted chemical etching to form a Si NWs array integrally connected with the silicon substrate; (3) Preparation of TiO2 seed layer: The titanium-containing precursor liquid is spin-coated onto the surface of the Si NWs array and heat-treated at 450~550 °C to form TiO2 seed layer; (4) Hydrothermal growth of TiO2 nanorods: Si NWs samples with TiO2 seed layers are placed in a hydrothermal reaction solution containing titanium source and hydrochloric acid, and hydrothermal reaction is carried out at 150~170℃. After cleaning and drying, the TiO2 nanorod modified Si NWs hierarchical array structure anode is obtained.
5. The preparation method according to claim 4, characterized in that, In step (1), the silicon wafer pretreatment includes: ultrasonically cleaning the silicon wafer in methanol and ethanol for 2-10 min in sequence, treating it in a mixture of concentrated sulfuric acid and hydrogen peroxide in a volume ratio of 3:1 for 100-150 min, and then treating it in a mixture of 40 wt.% hydrofluoric acid and water in a volume ratio of 1:3 for 5-10 min to remove the natural oxide layer on the surface.
6. The preparation method according to claim 4, characterized in that, In step (2), the concentration of silver nitrate is 0.01~0.03 M, the concentration of HF is 2~3 M, and the metal-assisted chemical etching is performed at room temperature for 100~150 min; After etching, the silicon wafer is placed in nitric acid for 4-6 minutes to remove residual silver.
7. The preparation method according to claim 4, characterized in that, In step (3), the titanium-containing precursor solution is composed of tetrabutyl titanate, acetylacetone, water, polyvinylpyrrolidone, and ethanol, wherein the molar ratio of acetylacetone, tetrabutyl titanate, and water is 0.2~0.5:1:0.5~2, the concentration of tetrabutyl titanate is 0.02~0.05 M, and the concentration of polyvinylpyrrolidone is 10~100 mg / L. 1 The spin coating speed is 3000~10000 rpm, the spin coating time is 20~60 s, and the heat treatment time is 1~3 h. Preferably, in step (4), the hydrothermal reaction solution is composed of hydrochloric acid, deionized water, and tetrabutyl titanate, with the concentration of tetrabutyl titanate being 0.036~0.055 mol / L. 1 The volume ratio of deionized water to concentrated hydrochloric acid is 0.8~1.2∶1, the hydrothermal reaction time is 1.5~3 h, and the Si NWs sample with TiO2 seed layer is placed vertically in the reaction vessel. Preferably, after the reaction in step (4) is completed, the reaction vessel is rapidly cooled by rinsing with cold water or by natural cooling, and the sample is taken out and rinsed with ethanol and deionized water in sequence and then dried.
8. A silicon-air battery, characterized in that, The anode of the TiO2 nanorod modified SiNWs hierarchical array structure as described in any one of claims 1-3, the air cathode, the membrane disposed between the anode and the air cathode, and the alkaline electrolyte.
9. The silicon-air battery according to claim 8, characterized in that, The alkaline electrolyte is 3 M KOH; the TiO2 nanorods of the TiO2 nanorod-modified Si NWs hierarchical array anode face the electrolyte.
10. The application of the TiO2 nanorod modified Si NWs hierarchical array structure anode according to any one of claims 1-3 in suppressing self-corrosion, hydrogen evolution and uneven passivation of silicon anodes in alkaline silicon-air batteries.
